Technology in Education: is it a technical issue only? - Elaine Conte; Rosa Maria Filippozzi Martini (Universidade Federal do Rio Grande do Sul, 2015)
This paper investigates the uses of technology in education, with reference to the dialogic resignification of senses and the socio-political and cultural relations of technologies in the constitution of the pedagogic discourse. It concerns to the investigation of the emblematic issues of the technology field used in education, glimpsing an education model that is sensitive to the prevention of the naive incorporation of technology in education. The study reviews conceptions to recognize the plurality and objectivity that have grounded pedagogical practices, elucidating how technological elements promote curiosity and interfere directly in the cultural formation, learning, language and all dimensions of human rationality.